The Security of Student Information Management System Based upon Blockchain. (21st April 2022) - Yang, Mingfeng; Wang, Jianying
Abstract : In recent years, with the development of science and technology, as an emerging data security technology, blockchain has been widely used in all walks of life by virtue of its immutability, uniqueness, smart contract, and decentralized organization. Examples include industry, services, and education. With the progress of China's education, the application of blockchain technology in the field of education has also been further expanded. At present, the application of blockchain in China's education field is mainly concentrated in three areas: education resource management, teaching information management, and education basic platform construction. This article aims to study the security of the student information management system based on the blockchain. The security test experiment of the student information management system is carried out based on the encryption algorithm of the blockchain, and conclusions are drawn. The security of the student information management system based on the encryption algorithm of blockchain technology has increased by 87%, which also shows that the blockchain technology has a better effect on improving the security of the student information management system.